Visitando la matria: los cruces trasfronterizos de la población estadunidense de origen mexicano - Ruiz, Olivia (Frontera Norte, 2017)
Este trabajo es un primer paso en el análisis de la constitución de la cotidianidad étnica de la población de ascendencia mexicana que habita en la frontera Estados Unidos-México. Este escrito contribuye a esa labor, al examinar un fenómeno particular de la frontera: los cruces trasfronterizos. Se intenta ver de qué manera cambia la frecuencia, la duración y el propósito de los cruces, según el lugar de nacimiento, experiencia interurbana y nivel de ingreso.Se concluye que la experiencia interurbana y en menor grado el nacimiento en México, son los factores que más contribuyen a que se cruce a México y por implicación, que se desarrolle una mayor relación con aquel país. ABSTRACT This work is a preliminary step in the analysis of the day-to-day behavior of the Mexican-ancestry population living along the United States’ border with Mexico. This article contributes toward this broader aim by examining one particular behavioral phenomenon along the frontier: transborder crossings. The autor examines how the frequency of crossings, as well as the length of stay and purpose for the border crossings, vary by the border crosser’s place of birth, binational urban experiences, and income level. The article concludes with the finding that a crosser’s greater familiarity with urban centers on both sides of the border, and, to a lesser extent, birth in Mexico, makes it more likely that a U.S. resident of Mexican ancesty will integrate closely with Mexico, evidence in a pattern of more frequent crossings of the international frontier.